Demonstration of a desk-top size high repetition rate soft x-ray laser - Heinbuch, S., author; Martz, D., author; Grisham, M., author; Rocca, Jorge J., author; Optical Society of America, publisher (Colorado State University. Libraries, 2005)
We have demonstrated a new type of high repetition rate 46.9 nm capillary discharge laser that fits on top of a small desk and that it does not require a Marx generator for its excitation. The relatively low voltage required for its operation allows a reduction of nearly one order of magnitude in the size of the pulsed power unit relative to previous capillary discharge lasers. Laser pulses with an energy of ~ 13 μJ are generated at repetition rates up to 12 Hz. About (2-3) × 104 laser shots can be generated with a single capillary. This new type of portable laser is an easily accessible source of intense short wavelength laser light for applications.